COUNTERING RELIGIOUS RADICALISM: STRATEGIC STEPS OF THE ISLAMIC EDUCATION DEPARTMENT AT IAIN PONTIANAK - Kurniawan, Syamsul (Jurnal Pendidikan, Kebudayaan dan Keislaman, 2025)
This article examines the strategic steps taken by the Islamic Education Department (PAI) at IAIN Pontianak to counter religious radicalization among students. The primary focus of this study is the department’s efforts to educate students through a religious moderation-based curriculum, aimed at preventing narrow and exclusive interpretations of religion. A qualitative-descriptive approach is used in this research, combining field research methods with a systematic literature review. The study finds that the PAI department is dedicated to developing a curriculum that incorporates the values of Islamic moderation while also leveraging technology to expand students' perspectives on pluralism and multiculturalism. Education programs rooted in moderate values, such as Religious Moderation Education, play a key role in fostering tolerance and harmony among religious communities. However, the main challenge faced is the limited resources of faculty and facilities needed to support the effective implementation of this curriculum. The significance of this research lies in its contribution to discussions on Islamic education, especially in strengthening religious moderation within Islamic higher education. This article also offers a new perspective on the critical role of curriculum, faculty, and technology in addressing the challenges of radicalization, making it highly relevant for Islamic education that emphasizes inclusive values and multiculturalism. Artikel ini mengkaji langkah-langkah strategis yang dilakukan oleh Prodi Pendidikan Agama Islam (PAI) di IAIN Pontianak dalam menangkal radikalisasi agama di kalangan mahasiswa. Fokus utama penelitian ini adalah upaya Prodi dalam mendidik mahasiswa melalui kurikulum berbasis moderasi beragama yang bertujuan mencegah munculnya penafsiran agama yang sempit dan eksklusif. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan memadukan metode penelitian lapangan dan telaah pustaka secara sistematis. Hasil penelitian menunjukkan bahwa Prodi PAI berkomitmen mengembangkan kurikulum yang mengintegrasikan nilai-nilai moderasi Islam sekaligus memanfaatkan teknologi untuk memperluas wawasan mahasiswa mengenai pluralisme dan multikulturalisme. Program pendidikan yang berakar pada nilai-nilai moderat, seperti Pendidikan Moderasi Beragama, berperan penting dalam menumbuhkan sikap toleransi dan harmoni antarumat beragama. Namun, tantangan utama yang dihadapi adalah keterbatasan sumber daya dosen serta sarana dan prasarana yang diperlukan untuk mendukung implementasi kurikulum secara efektif. Signifikansi penelitian ini terletak pada kontribusinya terhadap diskursus pendidikan Islam, khususnya dalam memperkuat moderasi beragama di perguruan tinggi Islam. Artikel ini juga menawarkan perspektif baru mengenai peran penting kurikulum, dosen, dan teknologi dalam menghadapi tantangan radikalisasi, sehingga relevan bagi pengembangan pendidikan Islam yang menekankan nilai inklusif dan multikulturalisme.